Dogs with sepsis are more hypercoagulable and have higher fibrinolysis inhibitor activities than dogs with non-septic systemic inflammation - Emily Hill; Yao Zhu; Marjory B. Brooks; Robert Goggs; Robert Goggs (Frontiers in Veterinary Science)
IntroductionHemostatic imbalance in dogs with sepsis is characterized by hypercoagulability and hypofibrinolysis. We aimed to determine whether these abnormalities are unique features of sepsis or are also present in dogs with non-septic critical illness. Secondary aims were to assess relationships between coagulation assay results and circulating markers of neutrophil extracellular traps (NETs), and to relate coagulation assay abnormalities with survival in dogs with sepsis.MethodsThis prospective single-center observational cohort study enrolled 55 client-owned dogs that satisfied at least 2 systemic inflammatory response syndrome (SIRS) criteria. Dogs with a bacterial infection were categorized as sepsis, those without evidence of infection were categorized as non-infectious systemic inflammation (nSIRS). Clotting times, fibrinogen and D-dimer concentrations, and activities of antithrombin (AT), antiplasmin (AP), thrombin activatable fibrinolysis inhibitor (TAFI), and total and active plasminogen activator inhibitor-1 (PAI-1) were measured. Thrombin generation and overall hemostasis potential assays were performed and concentrations of cell-free DNA (cfDNA) and H3.1 nucleosomes quantitated.ResultsCompared to dogs with nSIRS, dogs with sepsis had higher fibrinogen concentrations, greater endogenous thrombin potential, higher AP and TAFI activities and greater overall hemostasis and coagulation potential values. H3.1 nucleosome and cfDNA concentrations were strongly correlated and significantly associated with various coagulation variables. In dogs with sepsis, non-survivors had lower AT activity, and higher active PAI-1 and H3.1 nucleosome concentrations.DiscussionRelative to non-septic critically ill dogs, dogs with sepsis are hyperfibrinogenemic, hypercoagulable and have higher AP and TAFI activities. Concentrations of H3.1 nucleosomes and active PAI-1 and AT activity might have prognostic value in dogs with sepsis.